Market access in Russia for foreign investors: advantages and disadvantages - M. G. Sukhorukova (Путеводитель предпринимателя, 2020)
This article is dedicated to the analysis of the basic forms of Market access in Russia. Different types of the market access for foreign companies have been considered, advantages and disadvantages of each types of localization have been analyzed, as well as the main problems faced by foreign companies in the process of localization have been revealed.